A Guideline for Game Development-Based Learning: A Literature Review - Bian Wu; Alf Inge Wang (International Journal of Computer Games Technology)
This study aims at reviewing the published scientific literature on the topics of a game development-based learning (GDBL) method using game development frameworks (GDFs) with the perspective of (a) summarizing a guideline for using GDBL in a curriculum, (b) identifying relevant features of GDFs, and (c) presenting a synthesis of impact factors with empirical evidence on the educational effectiveness of the GDBL method. After systematically going through the available literature on the topic, 34 relevant articles were selected for the final study. We analyzed the articles from three perspectives: (1) pedagogical context and teaching process, (2) selection of GDFs, and (3) evaluation of the GDBL method. The findings from the 34 articles suggest that GDFs have many potential benefits as an aid to teach computer science, software engineering, art design, and other fields and that such GDFs combined with the motivation from games can improve the students’ knowledge, skills, attitudes, and behaviors in contrast to the traditional classroom teaching. Furthermore, based on the results of the literature review, we extract a guideline of how to apply the GDBL method in education. The empirical evidence of current findings gives a positive overall picture and can provide a useful reference to educators, practitioners, and researchers in the area of game-based learning.